Sustainable Development Based Tourism Governance Development Policy - Thariq Farhan Pudianto Prabowo (UNIFIKASI : Jurnal Ilmu Hukum, 2021)
This study aims to describe tourism governance development policies in Karanganyar Regency and the concept of sustainable development-based tourism policy and governance. The research employed empirical juridical approach. Therefore, this research focused on primary data collected from the interview and observation. In addition, this research was also supported by secondary data collected from literature study. Finally, the data were analyzed qualitatively. The findings revealed that the tourism governance development policies in Karanganyar regency which stated in the laws and regulations are adequate. However, its implementation is not yet running well. Furthermore, the sustainable development-based tourism governance development policy is the state's responsibility. The state acts as the holder of natural resource power and strengthens the community rights as the holders of state sovereignty. In conclusion, the tourism governance development policies in Karanganyar Regency cover environmental-friendly tourism development. However, its implementation has not yet been realized by the government of the Karanganyar regency. Moreover, the concept of sustainable development-based tourism governance development policy is based on the following basic principles, the state’s responsibility as the holder of natural resource power and strengthens the community right as the holders of state sovereignty